2001
DOI: 10.1038/sj.gt.3301465
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin-4 but not of interleukin-10 from a replicative herpes simplex virus type 1 viral vector precludes experimental allergic encephalomyelitis

Abstract: We have used interleukin (IL)-4 and -10-producing HSV-1 ␥ 1 34.5 deletion viruses in gene therapy of a BALB/c model of experimental allergic encephalomyelitis (EAE), a T cellmediated demyelinating disease of the central nervous system. It is known that in EAE of mice the Th2-type cytokines are down-regulated and the Th1-type cytokines up-regulated during the onset and relapse of the disease. Therefore, we tested two HSV-1 recombinants expressing the Th2-type cytokines IL-4 and IL-10. The recombinant viruses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
(48 reference statements)
3
31
0
Order By: Relevance
“…[25][26][27][28] Along with others, we have previously used intrathecally or intracranially delivered Th2 cytokine-expressing HSV vectors for treatment of EAE. [26][27][28][29][30] Still, mice lacking the IL-4 gene have shown variable susceptibility to EAE, depending on mouse strain. 31,32 Studies with IL-10-deficient mice have, on the other hand, shown that IL-10 is critical in the regulation of EAE.…”
Section: Multiple Sclerosis (Ms) Is a Demyelinating Autoimmune Diseasmentioning
confidence: 99%
“…[25][26][27][28] Along with others, we have previously used intrathecally or intracranially delivered Th2 cytokine-expressing HSV vectors for treatment of EAE. [26][27][28][29][30] Still, mice lacking the IL-4 gene have shown variable susceptibility to EAE, depending on mouse strain. 31,32 Studies with IL-10-deficient mice have, on the other hand, shown that IL-10 is critical in the regulation of EAE.…”
Section: Multiple Sclerosis (Ms) Is a Demyelinating Autoimmune Diseasmentioning
confidence: 99%
“…Gene therapy has not yet been attempted in MS, but there have been a number of studies in EAE that have invariably shown some level of efficacy at inhibiting the disease (Table 1), although in many cases this has only been an amelioration rather than elimination of disease. As the majority of the CNS is postmitotic, this puts constraints on the nature of the vector that can be used, and to date administration of plasmid DNA, [32][33][34][35][36][37][38][39][40][41] viral infection, [42][43][44][45][46][47][48][49][50][51][52][53] and retrovirally transduced cell (RVC)-carriers 47,[54][55][56][57][58][59][60][61][62][63] have been investigated in EAE (Table 1). These have largely focused on inhibition of the immune response either applied centrally to target the local pathological events within the CNS or peripherally administered to inhibit: initial sensitization, the activities of circulating cells or perivascular events in areas of local BBB breakdown.…”
Section: Gene Therapy In Autoimmune Demyelinating Diseasementioning
confidence: 99%
“…34 In contrast, replication-deficient viral vectors such as adenoviral (AV) and herpes simplex viral (HSV) vectors, which can infect postmitotic cells, can reliably produce secreted protein. Intracisternal [50][51][52][53] or intraventricular 46 delivery of viral vectors shows significant and efficient transduction of the ependymal cell layer that surrounds the brain ventricles and spinal canal. 64 The intracisternal (ependymal) delivery also targets the choroidal and leptomeningial cells coating the brain and spinal cord and is therefore a useful target for delivering soluble molecules that consistently reaches all CSF spaces and avoids infection of neurons.…”
Section: Local Immunogene Therapy In Cns Autoimmunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of adjuvant-induced arthritis in rats pretreated with HSV vector encoding PAPP resulted in improved locomotion, reduced hyperalgesia and slowed the progression of bone destruction when compared to control animals. 67 HSV replication-deficient vectors encoding IL-4 have demonstrated therapeutic effect after onset of disease in mouse 68,69 and primate models 70 of EAE. Similarly, fibroblast growth factor-II encoded from HSV reversed disease in a mouse model of EAE.…”
Section: Adeno-associated Virusmentioning
confidence: 99%